National Creutzfeldt–Jakob disease research biobank, a novel approach to the establishment of the scientific platform: collaboration between patient advocacy group, scientists, regulators and physicians - Alice Anane; Doron Pasternak; Shimon A. Reisner; Victor Novack (Orphanet Journal of Rare Diseases)
Abstract Creutzfeldt–Jakob disease (CJD) is a severe neurodegenerative disorder characterized by the abnormal accumulation of prion proteins. In Israel, a unique epidemiological pattern of CJD has been identified, specifically a genetic form (gCJD) associated with the E200K mutation in the PRNP gene. Investigating rare diseases such as CJD syndrome poses challenges due to their low prevalence, hindering the formation of an adequate patient cohort for comprehensive research and treatment trials. To overcome this limitation, biobanks have emerged as transformative tools for collecting and distributing biological specimens along with corresponding health data. Biobanks offer a solution to the inherent heterogeneity in rare diseases, allowing researchers to access diverse and extensive sample sets, thereby enhancing the understanding of disease nuances toward potential therapy. We introduce a novel collaborative model involving the Negev BioBank (NBB), the Creutzfeldt–Jakob Israel Foundation, the Israeli National BioBank for Research (MIDGAM), and the Israeli Ministry of Health. Each entity contributes unique expertise and resources to establish a comprehensive platform for studying the disease. The goal was to establish a participant pool of 500 individuals, including clinically diagnosed cases, confirmed carriers of the E200K mutation, and their first- and second-degree relatives. During the pilot phase of the last year, 250 participants were enrolled, with each family contributing between 1 and 25 participants. This collaborative approach involving communities, scientists, physicians, and regulatory bodies establishes a model applicable across various fields. These synergistic efforts aim to advance research on CJD and potentially serve as a blueprint for studying other rare diseases.